Filtered Log-periodogram Regression of long memory processes - Yuanhua Feng; Jan Beran (University of Konstanz, Center of Finance and Econometrics (CoFE), 2008)
Filtered log-periodogram regression estimation of the fractional differencing parameter d is considered. Asymptotic properties are derived and the effect of filtering on ˆd is investigated. It is shown that the estimator by Geweke and Porter-Hudak (1983) can be improved significantly using a simple family of filters. The essential improvement is based on a binary decision that is asymptotically correct with probability one. The idea is closely related to the well known technique of pre-whitening.
urn:nbn:de:bsz:352-opus-116770
Keywords: 330; Filtering; log-periodogram regression; local pre-whitening; fractional differencing parameter; long memory